Autoimmune destruction of pericytes as the cause of diabetic retinopathy - Duncan D Adams (Dove Medical Press, 2008)
Duncan D AdamsFaculty of Medicine, University of Otago, Dunedin, New ZealandAbstract: In diabetic retinopathy, collapse of the retinal vasculature is associated with loss of the pericytes. These are contractile cells that together with endothelial cells form the terminal arterioles of the retina. The cause of the loss of pericytes is not known. Recently, it has been discovered that type 1 diabetes is caused by forbidden clones of cytotoxic T lymphocytes, which destroy the insulin-making cells with exquisite specificity. In the light of this, I postulate that an antigenically-related forbidden clone of cytotoxic T lymphocytes selectively destroys the pericytes and that this is the cause of the vascular collapse of diabetic retinopathy. If this is so, the therapeutic implications are immense, involving a switch from ineffectual tight glycemic control to immunotherapy. This is already used as immunosuppression to prevent organ transplant rejection, and as the immune ablation and autologous bone marrow cell reconstitution that has saved the lives of patients with lethally-severe scleroderma. Once the pericyte surface auto-antigen for the T lymphocytes has been isolated, selective destruction of the pathogenic T lymphocytes would be possible by manufacture and use of cytotoxic auto-antigen complexes, which arrests progression of the retinopathy.Keywords: pericytes, diabetic retinopathy, autoimmunity, T cell forbidden clones, immunotherapy